Playing a Strategy Game with Knowledge-Based Reinforcement Learning - Voss, Viktor; Nechepurenko, Liudmyla; Schaefer, Rudi; Bauer, Steffen (SN computer science, 2020)
This paper presents knowledge-based reinforcement learning (KB-RL) as a method that combines a knowledge-based approach and a reinforcement learning (RL) technique into one method for intelligent problem solving. The proposed approach focuses on multi-expert knowledge acquisition, with the RL being applied as a conflict resolution strategy aimed at integrating the knowledge of multiple exerts into one knowledge base. The article describes the KB-RL approach in detail and applies the reported method to one of the most challenging problems of current artificial intelligence research, namely playing a strategy game. The results show that the KB-RL system is able to play and complete the full FreeCiv game, and to win against the computer players in various game settings. Moreover, with more games played, the system improves the gameplay by shortening the number of rounds that it takes to win the game. Overall, the reported experiment supports the idea that, based on human knowledge and empowered by RL, the KB-RL system can deliver a strong solution to the complex, multi-strategic problems, and, mainly, improve the solution with increased experience.